Manufacturing of Microfluidic Sensors Utilizing 3D Printing Technologies: A Production System - ÇELEBİ, MEHMET FATİH; ERSOY, SEZGİN (HINDAWI LTD, 2021)
3D integrated microfluid devices are a group of engineered microelectromechanical systems (MEMS) whereby the feature size and operating range of the components are on a microscale. These devices or systems have the ability to detect, control, activate, and create macroscale effects. On this basis, microfluidic chips are systems that enable microliters and smaller volumes of fluids to be controlled and moved within microscale-sized (one-millionth of a meter) channels. While this small scale can be compared to microfluid chips of larger applications, such as pipes or plumbing practices, their small size is commonly useful in controlling and monitoring the flow of fluid. Through such applications, microfluidic chip technology has become a popular tool for analysis in biochemistry and bioengineering with their most recent uses for artificial organ production. For this purpose, microfluidic chips can be instantly controlled by the human body, such as pulse, blood flow, blood pressure, and transmitting data such as location and the programmed agents. Despite its vast uses, the production of microfluidic chips has been mostly dependent upon conventional practices that are costly and often time consuming. More recently, however, 3D printing technology has been incorporated in rapidly prototyping microfluid chips at microscale for major uses. This state-of-the-art review highlights the recent advancements in the field of 3D printing technology for the rapid fabrication, and therefore mass production, of the microfluid chips.
Keywords: 2-PHOTON POLYMERIZATION; DIRECT-WRITE; MEMS; FABRICATION; CHIP; DEPOSITION; ORIGINS; SILICON; DESIGN; FUTURE